Comparison of colonoscopic performance between medical and nurse endoscopists: a non-inferiority randomised controlled study in Asia. Issue 7 (18th December 2014) - Hui, Aric J; Lau, James Y; Lam, Phyllis P Y; Chui, Alman O M; Fan, Alice S H; Lam, Thomas Y T; Tse, Yee-kit; Tang, Raymond S Y; Ng, Siew C; Wu, Justin C Y; Ching, Jessica Y L; Wong, Martin C S; et al.
Abstract : Objective: To test the hypothesis that trained nurse endoscopists are not inferior to medical endoscopists in finding adenomas during colonoscopy. Design: This is a prospective, randomised, single-blind, non-inferiority study comparing nurses with medical endoscopists in performing screening colonoscopy. The nurse endoscopists had been trained according to the British Joint Advisory Group on GI Endoscopy curriculum and had completed at least 140 colonoscopic procedures prior to the study. The primary endpoint was the adenoma detection rate. Secondary endpoints included the caecal intubation rate, intubation time, complication rate, patient pain and satisfaction scores. Results: We enrolled and analysed a total of 731 patients over a 15-month period. At least one adenoma was found in 159 (43.8%) of 363 patients by nurse endoscopists and 120 (32.7%) of 367 patients by medical endoscopists and a proportion difference of +11.1% compared with the medical endoscopists (95% CI 4.1% to 18.1%). The withdrawal time was, however, significantly longer among nurses (998 vs 575 s, p<0.001). After adjusting for differences in a regression analysis, colonoscopy by nurses was associated with a lower adenoma detection rate (OR 0.475: 95% CI 0.311 to 0.725). Nurse endoscopists had a lower caecal intubation rate (97.3% vs 100%), received better pain and satisfaction scores and had a high rate of patient acceptance. Conclusions: In this pragmatic trial, nurses can perform screening colonoscopy but require a longer procedural time to achieve a comparable adenoma detection rate as medical endoscopists. Trial registration number: NCT01923155.